1996
DOI: 10.1021/ac951253r
|View full text |Cite
|
Sign up to set email alerts
|

Proton:  A Major Factor for the Racemization and the Dehydration at the Cyclization/Cleavage Stage in the Edman Sequencing Method

Abstract: The racemization of the liberated 7-[(N,N-dimethylamino)sulfonyl]-4-(2,1,3-benzoxadiazolyl)-thiazoli none (DBD-TZ) amino acid during the cyclization/cleavage reaction with trifluoroacetic acid (TFA) in the Edman sequencing procedure has been carefully investigated, and evidence is presented to show conclusively that the racemization is caused by the replacement of a hydrogen atom by TFA. The fluorescent reagent 7-[N,N-dimethylamino)sulfonyl]-4-(2,1,3-benzoxadiazolyl) isothiocyanate (DBD-NCS) was used for amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…Recently, the peptides or proteins containing D-amino acids were found, and therefore the method for the amino acid sequence and D/L-configuration determination were studied . At the cyclization and cleavage reaction, the use of boron trifluoride-etherate (BF 3 ) instead of TFA suppresses the racemization of DBD-TZ derivatives (Matsunaga et al, 1996a) and the method for the amino acid sequence and D/L-configuration determination were established using DBD-NCS (Matsunaga et al, 1996b). The reports on the comparison of DBD-NCS with other benzofurazan isothiocyanates reported that DBD-NCS was the most suitable reagent for the detection of TZ derivatives (Matsunaga et al, 1997;Toriba et al, 1999).…”
Section: For Carboxylic Acids Nbd-pzmentioning
confidence: 99%
“…Recently, the peptides or proteins containing D-amino acids were found, and therefore the method for the amino acid sequence and D/L-configuration determination were studied . At the cyclization and cleavage reaction, the use of boron trifluoride-etherate (BF 3 ) instead of TFA suppresses the racemization of DBD-TZ derivatives (Matsunaga et al, 1996a) and the method for the amino acid sequence and D/L-configuration determination were established using DBD-NCS (Matsunaga et al, 1996b). The reports on the comparison of DBD-NCS with other benzofurazan isothiocyanates reported that DBD-NCS was the most suitable reagent for the detection of TZ derivatives (Matsunaga et al, 1997;Toriba et al, 1999).…”
Section: For Carboxylic Acids Nbd-pzmentioning
confidence: 99%
“…This difference in detection sensitivity should be caused by the efficiency of the reaction, loss of the peptides on the membranes and/or absorption of the CIP-TZ-amino acids on the membranes, since the present system involves solid-phase reaction, washing with and extraction steps. Most importantly, there was no evidence for the dephosphorylation or degradation of phosphorylated CIP-TZ amino acids as has been reported in conventional Edman procedures [27].…”
Section: Identification Of Cip-tz Amino Acidsmentioning
confidence: 63%
“…The racemization at the a-carbon position occurred in a protic solvent such as TFA via keto-enol tautomerizations (Matsunaga et al, 1996). To suppress the racemization, BF 3 , an aprotic Lewis acid, was used instead of TFA in the cyclization/cleavage step.…”
Section: Simultaneous Determination Methods For Sequencing and Con®gurmentioning
confidence: 99%
“…To suppress the racemization, BF 3 , an aprotic Lewis acid, was used instead of TFA in the cyclization/cleavage step. When BF 3 was used as the cyclization/cleavage reagent, the racemization ratios of amino acid residues were less than 2.5% during the Edman procedure (Matsunaga et al, 1996). Also, the racemization was affected by the structure of the Edman reagents.…”
Section: Simultaneous Determination Methods For Sequencing and Con®gurmentioning
confidence: 99%
See 1 more Smart Citation